A review of the management of perforated duodenal ulcers at a tertiary hospital in south western Nigeria - Etonyeaku, AC (Makerere Medical School, 2013)
BACKGROUND: Gastro-duodenal perforations are common and may complicate peptic ulcer disease. Management is often by surgical closure. OBJECTIVE: To determine the patterns of presentation and mode of management of duodenal ulcer perforations. METHODS: Retrospective review of patients with duodenal ulcer perforations seen at the Obafemi Awolowo University Teaching Hospital between June 2001 and July 2011. Patients' records were reviewed for demography, duration of disease, probable risk factors, type of surgery and complications. Data obtained was analyzed using SPSS 15.0. RESULT: Forty- five patients were reviewed. There were 37 males (82.2%). Mean age was 39.7years (range 15–78years). There were 10 (22.6%) students and 8(17.8%) farmers. NSAIDs abuse (11), previous peptic ulcer disease (2), and no prior dyspeptic symptoms (20) constituted 24.4%, 4.4% and 44.4% respectively of cases. Seven (16%) patients presented less than 24 hours of onset of illness. Forty one perforations (91.1%) involved the first part of duodenum. Twenty two (49%) patients had Graham's omental patch. We had one (2.2%) failed repair and six (13.3%) mortalities. CONCLUSION: Late presentation of duodenal ulcer perforation is common with high mortality. Pragmatic surgical intervention with Graham's omentopexy with broad spectrum antibiotics is still commonly practiced.